ANALISIS YURIDIS PENYELESAIAN SENGKETA TERHADAP PERJANJIAN BAGI HASIL DALAM USAHA PENJUALAN PAKAIAN JADI ANTARA PEMILIK DAN PENGELOLA TOKO (STUDI KASUS PASAR ULEE GLEE DI KECAMATAN ULEE GLEE) - MUHAMMADAN MUHAMMADAN (PREMISE LAW JURNAL, 2016)
Contract follows the general provisions stipulated in Article 1320 in Civil Code the valid conditions of a contract, the profit sharing contract which includes rights and liabilities of each party, risks, time length, profit sharing, and forms of profit sharing.The problems of the research how about the legal position of a contract in ready-made garment business, what factors which caused the violation against profit sharing contract in ready-made garment business, and how about the settlement of dispute in profit sharing contract in ready-made garment business. The research used descriptive analytic and judicial empirical approach. The result of the research shows that profit sharing contact of ready-made garment business at Pasar Ulee Glee is made according to the agreement of the parties concerned orally which is valid as it is stipulated in Article 1320. The factors that caused the contract which did not run in line with the prevailing provisions were that they were made based on the custom, Therefore, this would create possibilities for any conflict to occur which might end up with dispute among parties, settlement of this problem was made with non litigation way through mediation process according to the customs which was helped by a mediator, namely Geuchik Gampong using the system of duek pakat (a meeting for all parties in dispute). Keywords: Profit Sharing Contract, Settlement of Dispute